SEJARAH DAN AKTIVITAS KEAGAMAAN DI MASJID AL-LATHIIF KOTA BANDUNG TAHUN 1966-2015 - DENISYA AZZURA; DANI WARDANI (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2024)
Mosques are centers of religious activities for Muslims. Currently, mosque construction is growing rapidly, with many mosques standing tall both in urban and rural areas. From the mosque, Islamic civilization began to develop, and throughout its history, mosques have had an important role in the lives of Muslims. At the beginning of his preaching in Medina, the Prophet chose the mosque as the main center for all Muslim activities in advancing civilization. The history of the mosque began not long after the Prophet moved to Medina, where his first step was to invite his followers to build a mosque. Based on the description above, the researcher intends to conduct research with the problem formulation (1) How is the Mosque as a System of Religious Social Institutions? (2) History of the founding of the Al-Lathiif Mosque in Bandung City? (3) How did the Al-Lathiif Mosque in Bandung City function from 1966-2015? This research includes historical research using a qualitative approach. Which includes Heristics, Criticism, Interpretation and Historiography. In collecting data, the author used interview, observation and documentation methods as data collection techniques